Micro-scale properties of cement pastes exposed to gamma radiation - Jiří Němeček; Andrea Špaková; Jiří Němeček; Patricie Halodová (Acta Polytechnica CTU Proceedings, 2025)
The extension of the lifetime of nuclear power plants is a critical issue today, raising concerns about the microscale mechanisms and mechanical changes in the individual phases of concrete that contribute to its macroscopic deterioration. Accurate quantification of these changes is essential for more reliable lifetime predictions. This paper investigates the effects of gamma irradiation on cement pastes exposed to varying relative humidity levels (RH = 11–100 %) using scanning electron microscopy (SEM) and nanoindentation. While SEM analysis did not reveal significant phase changes through image analysis, nanoindentation highlighted substantial differences in the mechanical properties of samples exposed to either low or high humidity or submerged in water during irradiation.